Citizens’ involvement in risk management: the view of community members (Italian Journal of Public Health, 2010)
Background: Industrial risk management plays a central role in creating supportive environments for health.This paper examines the community’s trust in citizens’ involvement in risk management, investigatingdifferences among settings exposed to different levels of industrial risk. Additionally it aims to identifythe social demographic characteristics of those manifesting high trust in citizens’ involvement in riskmanagement.Methods: The survey, performed in Sardinia between 2006 and 2007, was carried out in three representativeareas this Region: a metropolitan area, an industrial area, and a rural area. A questionnaire was administeredto 1,104 citizens to investigate community’s trust in citizens as “risk managers”.Results: Trust in citizens’ involvement in risk management was expressed to a greater extent by residents inthe rural area, by those with a high level of education, and by older women. The expression of high trust incitizens’ involvement was more likely in older higher-educated women (58-69%) than in lower educated ones(52-63%) and, to a lesser extent, in both genders with higher education (42-51%).Conclusions: A consistent number of the community’s members would entrust citizens with risk managementnot only in areas with a severe industrial impact, but also in those areas where industrial risk is consideredof limited entity. The community’s tendency towards citizens’ involvement in risk management appears to bean intrinsic trait of the community itself rather than an attitude triggered by a specific problem. Older women,and adults with higher education can be recognised as categories in which potential early adopters of riskmanagement can be easily found.
Keywords: risk management; trust; socioeconomic context